Efecto de physalis peruviana sobre la lipoperoxidación inducida en membranas de células hepáticas de rattus norvegicus var. albinus ooforectomizadas - Delgado Fernández, Jimmy Jack (2014)
In the present research work there decided the effect of the fruit of Physalis peruviana (aguaymanto) on the lipoperoxidación induced in membranes of hepatic cells of Rattus norvegicus var. albinus ooforectomizadas. 24 Rattus norvegicus var. albinus was used from 2 until 3 months of age, previously ooforectomizadas; which were distributed in groups; control, boss(pattern), problem 1 and 2. Oral route was administered: to the group control NaCl l0.9 %, to the group boss(pattern), fluoxetina 20 mg/kg and to the groups problem 1 and 2, juice of Physalis peruviana 1.5 g/kg and 3 g/kg p.c of the treatment respectively, for a period of three weeks; 1 week later one proceeded to sacrifice them and extract the hepatic samples that served for the determination of the effect of Physalis peruviana on the lipoperoxidación by means of the measurement of the levels of malondialdehido, using the colorimetric method of the thiobarbituric acid reactive substances (TBARS), with readings to 532 nm of wavelength; the results were processed, and then they were analyzed as per statistics with the method ANOVA; at a significancia level (p ≤ 0.05), being observed a significant difference between all the groups; the void hypothesis being rejected the alternative hypothesis being accepted, then it was corroborated by the test of Tukey, where it is demonstrated that Physalis peruviana to dose of 3.0 g/kg presents protective effect in the lipoperoxidación induced in membranes of hepatic cells of Rattus norvegicus var. albinus ooforectomizadas, compared to the group boss(pattern) (p≤0.05).